Effects of Light-Emitting Diodes Light Quality on Growth, Development and Metabolism of Wheat (Triticum Aestivum L.) Seedlings - LIU, Yongqiang; Sun, Kelong; Peng , Ying; Chen, Jianjun (Bangladesh Journal of Botany, 2023)
Light quality is considered crucial for plant growth, development and metabolism. The objective of this study was to investigate the impact of different light-emitting diodes (LEDs) light qualities on the growth of wheat (Triticum aestivum L.) seedlings. Five different set of LEDs light quality namely CK, 5R1B, 4R2B1G, 3B3R, 4B2R and 4B2R1G were used. The morphology, stomatal characteristic, biomass accumulation, RubisCO enzyme activity, photosynthetic pigment, value, soluble sugar and protein, Malondialdehyde (MDA ) root activity and others were measured with CK as the control. The results showed that the fresh weight, RubisCO enzyme activity, photosynthetic pigment accumulation, soluble sugar content and stomatal length in 5R1B treatment were higher than other treatment group, which increased by 1, 47, 57 and 18%, respectively compared to CK,. This indicated that 5R1B treatment group is most conducive to plant growth and photosynthesis, and does not cause lipid peroxidation damage to wheat seedlings under light treatment. Bangladesh J. Bot. 51(4): 987-993, 2022 (December) Special